Microwave Planar Sensor for Permittivity Determination of Dielectric Materials - Rammah Alahnomi; Natasha Binti Abd Hamid; Zahriladha Zakaria; Tole Sutikno; Amyrul Azuan Mohd Bahar (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This paper presents a single port rectangular ring resonator sensor for material characterizations. The proposed sensor is designed at operating resonance frequency of 4 GHz. The sensor consists of micro-strip transmission line and ring resonator with applying the enhancement method to the coupling gaps. The using of enhancement method is to improve the return loss of the sensor and sensitivity in terms of Q-factor, respectively. Furthermore, the proposed sensor is designed and fabricated on Roger 5880 substrate. Standard materials with known permittivity have been used in order to validate the sensor’s sensitivity. Based on the results, the percentage of error for the proposed rectangular sensor is 0.2% to 8%. It can be demonstrated that the proposed sensor will be useful for various applications such as medicine, bio-sensing and food industry.